2014
DOI: 10.1007/s11606-014-3102-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Race, Ethnicity, and Language Preference in an Electronic Health Record

Abstract: BACKGROUND: Collection of data on race, ethnicity, and language preference is required as part of the "meaningful use" of electronic health records (EHRs). These data serve as a foundation for interventions to reduce health disparities. OBJECTIVE: Our aim was to compare the accuracy of EHR-recorded data on race, ethnicity, and language preference to that reported directly by patients. DESIGN/SUBJECTS/MAIN MEASURES: Data collected as part of a tobacco cessation intervention for minority and low-income smokers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 13 publications
4
118
0
Order By: Relevance
“…As stated previously, to our knowledge, this is the first study to examine the relationship between social [7] to 7 %. On the contrary, personal blogging decreased slightly since 2007 from 7 to 6.4 %.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As stated previously, to our knowledge, this is the first study to examine the relationship between social [7] to 7 %. On the contrary, personal blogging decreased slightly since 2007 from 7 to 6.4 %.…”
Section: Discussionmentioning
confidence: 72%
“…A 2012 study revealed that among U.S. adult Internet users: 19 % reported using the Internet to track personal health information and 19 % reported emailing or communicating with their online healthcare providers electronically [7]. HIT engagement is more common among certain demographic groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians and staff frequently make errors when assigning ethnicity and ancestral origin to patients, especially if they do not rely on patient selfreport. 7 Ethnicity, religious affiliation, and location of origin are already imperfect surrogates for genetic diversity and will become even more so with increasing admixture. In addition, targeted screening runs the risk of reifying socially defined categories, while at the same time missing important genetic variation.…”
Section: © American College Of Medical Genetics and Genomicsmentioning
confidence: 99%
“…1 In this month's issue of JGIM, Klinger et al report important inaccuracies in REL data in electronic health records (EHRs) in 13 primary care clinics. 2 For example, 3 % and 6.6 % of patients who self-identified as Hispanic and African American, respectively, were not recorded as such in the EHR, and 20 % of persons documented in the EHRs as English-speaking elected to take a survey in Spanish. Inaccuracies in REL data have clustered around the distinction between Latino and black, American Indians, and multiracial categories, and lack of granularity among Asian American and Latino subgroups.…”
mentioning
confidence: 99%